Safety and efficacy of the CD95-ligand inhibitor asunercept in transfusion-dependent patients with low and intermediate risk MDS. (May 2018) - Boch, Tobias; Luft, Thomas; Metzgeroth, Georgia; Mossner, Maximilian; Jann, Johann-Christoph; Nowak, Daniel; Meir, Franziska La; Schumann, Christiane; Klemmer, Jennifer; Brendel, Susanne; Fricke, Harald; Kunz, Claudia; et al.
Highlights: Asunercept targets Fas/Fas ligand interaction. This is the first trial investigating the compound in patients with low and intermediate risk MDS. Given once a week at doses of 100 mg or 400 mg asunercept shows a very good safety profile. Asunercept shows biological activity in a subset of patients. No promotion of disease progression has been observed in this trial. Abstract: In low risk MDS, increased apoptosis of erythroid progenitors mediated via CD95 (Fas) activation has been described to result in peripheral cytopenia. Blockade of the CD95 system can improve erythropoiesis in MDS. Asunercept (APG101) is a fusion protein consisting of the extracellular domain of human CD95 and the Fc domain of human IgG1 blocking the interaction between CD95 and its ligand. Here we report on results from a phase I study in 20 transfusion-dependent low and intermediate risk MDS patients treated with intravenous asunercept (EudraCT 2012-003027-37). Primary objectives were safety and tolerability as well as pharmacodynamic effects. Secondary objectives were hematologic improvement, incidence and time to leukemic progression as well as overall survival. Frequency and severity of adverse events were in range of what could be expected in a patient cohort comprising of elderly MDS patients. Two patients experienced a serious adverse event with a suspected relationship to asunercept. The incidence of disease progression was low. In the 20 patients a decrease of the transfusion need from a mean of 10, 8 (±5, 1) pRBCs during the 12 weeks treatment phase to a mean of 10, 0 (±4, 2) pRBCs at the end of the study was observed. In conclusion, asunercept was well tolerated and showed efficacy in transfusion-dependent low and intermediate risk MDS patients. Further clinical investigation is warranted, particularly in combination with erythropoiesis stimulating agents (ESAs).